2022
DOI: 10.1142/s0218271822501267
|View full text |Cite
|
Sign up to set email alerts
|

Loop correction to the scalar Casimir energy density and generation of topological mass due to a helix boundary condition in a scenario with Lorentz violation

Abstract: In this paper, the effective potential approach in quantum field theory is used in order to investigate self-interaction loop correction to the Casimir energy density and generation of topological mass for both massless and massive real scalar fields. It is assumed that the scalar field obeys a helix boundary condition. In addition, it is also considered a CPT-even aether-type violation of the Lorentz symmetry. In the absence of the Lorentz violation, we obtain analytical expressions for the loop correction to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…It is important to note that the Casimir energy and its radiative correction for a massive and massless scalar field obeying helical boundary conditions in 3 + 1 dimensions were documented in Ref. [41]. In this context, we generalize our investigation to compute the leading order and its thermal correction to the Casimir energy for Lorentz-violated massive/massless scalar fields with helical boundary conditions in d + 1 space-time dimensions.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…It is important to note that the Casimir energy and its radiative correction for a massive and massless scalar field obeying helical boundary conditions in 3 + 1 dimensions were documented in Ref. [41]. In this context, we generalize our investigation to compute the leading order and its thermal correction to the Casimir energy for Lorentz-violated massive/massless scalar fields with helical boundary conditions in d + 1 space-time dimensions.…”
Section: Introductionmentioning
confidence: 63%
“…Another distinction in our computation of the radiative correction to the Casimir energy compared to those documented in Ref. [41] lies in the type of counterterm utilized. We employ the self-consistent renormalization program, which enables the derivation of counterterms consistent with the imposed boundary conditions, leading to counterterms that are position-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…For this, we took into account the non-trivial topology associated to the helical structure of the viral RNA strand. We have shown that this can be made by considering suited boundary conditions of the physical field involved in the problem as well as its quantum vacuum fluctuations, in accordance with Feng and Li, 2020 , Aleixo and Mota, 2021 and Farias Junior and Santana Mota (2022) .…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we compute the Casimir energy stored in the genome cylindrical-like segment corresponding to a helical pitch of the RNA molecule, then particularize the calculations to the SARS-CoV-2. For this, we will initially consider the quantum vacuum fluctuations of a scalar field under helix boundary conditions, in accordance with Feng and Li, 2020 , Aleixo and Mota, 2021 and Farias Junior and Santana Mota (2022) , extending the results to an electromagnetic field. In this context, in order to consider the most realistic situation, in our investigation we considered the UV-A and -C radiations as the threshold energy, since UV, during the day, is abundantly provided by the sun.…”
Section: Introductionmentioning
confidence: 99%
“…The analyses of the Casimir energy and topological mass associated with a massive scalar field in the LV scenario were considered in Refs. [31,32].…”
Section: Introductionmentioning
confidence: 99%